METODE ANIMASI TRANSISI SEBAGAI MEDIA REPRESENTASI PENGALAMAN PENGGUNA (USER EXPERIENCE) LINTAS GENERASI PADA IKLAN TOYOTA TOGETHER FOREVER - Satria Budiana Tresna; Chris Chalik; Anggar Erdhina Adi (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2026)
This study explores the implementation of transition animation techniques in the Toyota “Together Forever” advertisement to represent multi-generational user experiences in Indonesia. Within visual communication design, transitions serve as narrative instruments that bridge collective audience memories with brand identity. The research employs a descriptive qualitative method, integrating visual semiotic analysis and micro-level frame-by-frame observations. The investigation focuses on deconstructing technical elements, such as match-cuts and seamless transitions, to reveal how these components construct perceptions of vehicle comfort and reliability chronologically. The central issue addressed is the visual strategy used to communicate product value consistency amidst changing eras. Findings indicate that precise animation methods create a cohesive narrative, positioning brand loyalty as a non-fragmented experience. These techniques act as a temporal bridge, reinforcing Toyota's role within the history of Indonesian families. This study demonstrates that the synergy between animation methods and user psychology is vital for effectively delivering brand messages within today’s digital media ecosystem.